Financial technology and regulation: the competitive impact of open banking - Oscar Borgogno; Antonio Manganelli (Market and Competition Law Review)
Financial technology (FinTech) raises significant expectations in terms of ameliorated consumer welfare and competitive dynamics. A wide range of players is trying to harness the potential of this transition (including incumbents, startups, and so-called BigTechs with extensive customer networks, such as the Google, Amazon, Facebook, Apple). In the light of this, regulators and scholars are increasingly interested in new regulatory tools to address the challenges brought by technological innovation in the financial sector to consumer welfare and competition. The article contributes to these discussion by shedding light on the regulatory approaches to FinTech emerged so far. Further, the piece focuses on the pro-competitive effect of the access-to-account rule enshrined in the EU Directive 2015/2366 on payment services in the internal market (PSD2). This mechanism represents a very early sectorspecific regulatory attempt to nurture competition in the digital economy and effectively implement data sharing. In this regard, the on-going UK Open Banking market investigation remedy shows how the antitrust enforcement can be deployed to complement the regulatory toolkit